Age-related changes in insulin-like growth factor I and II in human femoral cortical bone: lack of correlation with bone mass - Seck, Thomas; Bretz, Anette; Krempien, Robert; Krempien, Burkhard; Ziegler, Reinhard; Pfeilschifter, Johannes (Bone, 1999)
The concentration of insulin-like growth factor-I (IGF-I) in human cortical bone declines with age, but the relevance of this decline for cortical bone turnover and bone mass is unknown. In the present study, we simultaneously assessed the concentration of IGF-I and -II in cortical bone matrix and histomorphometric parameters of bone mass and bone turnover in 125 samples from the proximal human femur shaft. Bone width decreased by 27% and porosity increased by 100% in female cortical bone between the fourth and the ninth decade. Similar, but weaker, changes tended to occur in male cortical bone. The concentrations of both IGF species were correlated with the percentage of osteons undergoing bone remodeling. However, despite age-related decreases in both IGF species in men and in IGF-I in women, neither of the IGFs accounted for age-related or age-independent variability in cortical porosity or bone width. In conclusion, these data suggest that the local concentrations of IGF-I and -II are related to cortical bone turnover. In contrast, our study provides no evidence for a major role of bone matrix IGF-I and -II as determinants of cortical bone mass in elderly individuals. Whether other components of the IGF system may be stronger determinants of cortical bone loss remains to be determined.
Gesehen am 14.05.2021